Negotiation Identity Ethnicity in the Midst of the Current Modernization: Study Qualitative in Minority Youth Generation - Danial Danial; Faza Achsan Baihaqi; Ryan Setiawan (Journal of Law, Social Science and Management, 2025)
Background: Ethnic identity plays a crucial role in shaping individual and collective consciousness, particularly among young generations in multicultural societies. In the era of modernization and globalization, identity becomes more dynamic, requiring continuous negotiation between traditional values and global cultural influences. Objective: This study aims to explore how young people from minority ethnic groups negotiate their ethnic identity amid modernization pressures, focusing on the roles of family, community, and digital media. Methods: A qualitative approach was employed, involving in-depth interviews with four informants from minority ethnic groups in Indonesia. The data were analyzed thematically to capture patterns of meaning and identity negotiation. Results: The findings reveal that ethnic identity is maintained through the use of local language, family-based cultural transmission, and active participation in community activities. Simultaneously, young people demonstrate adaptive strategies in multicultural settings while using social media and popular culture as platforms for creative identity expression. Modernization was found not to erase traditional values but to foster the emergence of hybrid identities that integrate both cultural heritage and global trends. Conclusion: Negotiation of ethnic identity among minority youth is a dynamic process influenced by traditional and modern factors. This highlights the importance of family, community, and digital platforms in sustaining ethnic identity.